Experimental alternatives for evaluation of progenies and clones in eucalyptus breeding programs - Magno Antonio Ramalho Patto (Revista Árvore, 2003)
The feasibility of using augmented block designs and spatial analysis methods for early stageselection in eucalyptus breeding programs was tested. A total of 113 half-sib progenies of Eucalyptus urophyllaand eight clones were evaluated in an 11 x 11 triple lattice experiment at two locations: Posto da Mata (Bahia,Brazil) and São Mateus (Minas Gerais, Brazil). Four checks were randomly allocated within each block. Plotsconsisted of 15 m long rows containing 6 plants spaced 3 m apart. The girth at breast height (cm/plant) wasevaluated at 19 and 26 months of age. Variance analyses were performed according to the following methods:lattice design, randomized complete block design, augmented block design, Papadakis method, moving meansmethod, and check plots. Comparisons among different methods were based on the magnitude of experimentalerrors and precision of the estimates of genetic and phenotypic parameters. General results indicated that augmentedblock design is useful to evaluate progenies and clones in early selection in eucalyptus breeding programs usingmoderate and low selection intensities. However, this design is not suitable for estimating genetic and phenotypicparameters due to its low precision. Check plots, nearest neighbour, Papadakis (1937), and moving means methodswere efficient in removing the heterogeneity within blocks. These efficiencies were compared to that in latticeanalysis for estimation of genetic and phenotypic parameters